Methods and current results of spinal tumor surgery - Yu. Yu. Polyakov; V. Ye. Olyushin; D. A. Gulyayev; M. M. Tastanbekov (Бюллетень сибирской медицины)
Spinal tumor surgery is one of the hardest neurosurgical branch, which requires microsurgical equipment and intraoperative monitoring. Spinal tumor diagnostics can be very difficult because of clinical signs same for other disease in case of acute clinical manifestation. Severity of disease is burdened with concomitant somatic symptomatology. According to histology, dissemination and vertebral lesion, each definite case should be examined individually and in complex. Only the surgical method is not enough for the decision of spinal tumor problem. It is obvious, than problem of pathogenesis, diagnostics and operative treatment of spinal cord tumors is task of current importance at present stage of neurological and neurosurgical development. This article presents surgery results for patients treated at Russian Neurosurgical Institute named after prof. A.L.Polenov, neurooncology department in period of time 1999—2007.